Ginsenoside Rg1 protects against aging-induced renal interstitial fibrosis due to inhibition of tubular epithelial cells endoplasmic reticulum stress in SAMP8 mice. (September 2020) - Ding, Shixin; Zhang, Han; Sun, Zhenghao; Han, Yuli; Li, Yan; Dong, Xianan; Yin, Yanyan; Li, Weiping; Li, Weizu
Graphical abstract: Highlights: ER stress involves in aging-related interstitial fibrosis in kidney aging in mice. Rg1 treatment significantly decreased renal interstitial fibrosis in SAMP8 mice. Rg1 treatment significantly inhibited ER stress in renal tissues in SAMP8 mice. Rg1 may be a potential agent for delaying the progression of kidney aging. Abstract: Aging has become a primary cause of chronic kidney diseases, which ultimately progress to renal interstitial fibrosis. Endoplasmic reticulum (ER) stress has been reported to participate in tubular epithelial cells injury. Ginsenoside Rg1 may have protective effects on kidney aging. In this study, we investigated the tubular interstitial fibrosis and ER stress change in aged mice, and further observed the effects of Rg1 on renal interstitial fibrosis and ER stress in SAMP8 mice. The results demonstrated that the ER stress, apoptosis and interstitial fibrosis were significantly increased in the tubular epithelial cells in 20-month-old (M) and 24M mice. Meanwhile, we found that Rg1 significantly attenuated the tubular epithelial cells ER stress, apoptosis and interstitial fibrosis in SAMP8 mice. This study suggested that ER stress and apoptosis were closely implicated with aging-related renal interstitial fibrosis in aging progression. Rg1 could ameliorate aging-related renal interstitial fibrosis via inhibiting ER stress and apoptosis.